Uso de la redes sociales (facebook, twitter, blog) como herramienta académica en los estudiantes de comunicación social de la Universidad Técnica de Cotopaxi en el periodo académico abril – agosto 2014 - Toaquiza Manzano, Milton Fabián (2015)
In this research the analysis of the importance of social networks like Facebook, twitter and blog as academic tools are exposed. In the first chapter develop the conceptually and bibliographic variables, used to thesis, and these are: The dependent variable, the academic tool and the independent variable, the use of Facebook, twitter and blog. In the second chapter we consider the topic of study and the sample in this researching work, we studied how the social communication students are with a sample of 180 students in four survey levels, the research sort was exploratory in field, The techniques used were surveys, to understand how the students use the social networks like Facebook, twitter and blog in their academic performance….